Health-Related Fitness Knowledge and Its Relation to College Student Physical Activity. (March 2017) - Sultoni, K; Jajat,; Fitri, M
Abstract: One area of studies that has been done in relation to improving physical activity (PA) is Health-related fitness knowledge (HRFK). The aim of this study was to examine HRFK of a college student and its relation to PA. An internet-based survey was conducted. The participants were 246 sophomore undergraduate students from Universitas Pendidikan Indonesia. HRFK was assessed using a test consisting of 21 multiple choice items. PA was assessed using International Physical Activity Questionnaire short form (IPAQ-SF). The result shows that HRFK college student is low. There is no significant correlation between HRFK and PA college student. Three is a slight possibility that knowledge of health-related fitness does not make someone more active physically.